(untitled) (Global Journal of Medical Research, 2023)
Background Stillbirth is one of the vital indicators of quality care it is one of the adverse outcomes of pregnancy and also it is a growing public health issues worldwide The outcome of delivery in Dekemhare Hospital has not been investigated The aim of the study was to determine the prevalence and determinants of stillbirth among women attended deliveries in Dekemhare Hospital Methods A facility-based unmatched case control study was conducted Cases were deliveries whose birth outcome was stillbirth and controls were deliveries with live birth A data extraction tool was developed to collect data from a sample of 552 138cases and 414 controls